Implementation of Professional Zakat among ASN at BAZNAS, Langkat Regency in 2018-2020 - Andriana Alnazhira Chandra; Zainul Fuad; Yenni Samri Juliati Nasution (Budapest International Research and Critics University, 2022)
This study aims to determine the implementation of professional zakat on the State Civil Apparatus in the Langkat Regency Government. This research is field research with data collection methods in the form of observations, interviews, and documentation. The data collected was processed and analyzed with descriptive qualitative. The results showed that: First, of the 8,535 State Civil Apparatus in the Langkat Regency Government, not all of them carried out their professional zakat, only some of the State Civil Apparatus were willing to deduct 2.5% of their salaries related to professional zakat, but only a few, such as high-class ASN, while others only donate and: Second, the receipt of professional zakat at the National Amil Zakat Agency (BAZNAS) is 50.29% of the funds channeled through 5 fields, namely education, health, humanity, economics as well as da'wah and advocacy. With the maximum collection of zakat/infaq funds by BAZNAS Kab. Langkat, the more distribution through these fields, which will be beneficial for the Mustahik in need.